Exploring the molecular mechanisms of the inhibition of acrolein-induced BEAS-2B cytotoxicity by luteolin using network pharmacology and cell biology technology. (February 2022) - Liu, Dan; Cheng, Ye; Chen, Junliang; Mei, Xueying; Tang, Zhipeng; Cao, Xiangyu; Liu, Jianli
Abstract: Acrolein is a highly reactive unsaturated hazardous air pollutant, which is extremely irritating to the respiratory tract. Luteolin, an active flavonoid compound, possesses multiple biological activities. The purpose of this study was to evaluate the mechanism of the inhibition of acrolein-induced human bronchial epithelial (BEAS-2B) cells cytotoxicity by luteolin using network pharmacology and cell biology technology. Firstly, network pharmacology results indicated that oxidative stress processes might play an important role in luteolin inhibiting lung injury. Next, it was verified at the cellular level. Reactive oxygen species (ROS) generation increased, glutathione (GSH) level decreased after exposure to acrolein. MAPK signaling pathways were activated, which activated downstream IκBα/NF-κB signaling pathways. Meanwhile, acrolein caused oxidative DNA damage and double-strand breaks, induced DNA damage response (DDR) and apoptosis. These adverse effects were significantly reversed by luteolin, which inhibited the activation of MAPK/IκBα/NF-κB and DDR pathways, and reduced the ratio of Bax/Bcl-2. Moreover, luteolin also had a similar effect to antioxidant N-acetyl cysteine (NAC) in the regulation of signaling transduction mechanisms, which indicated that the regulation of oxidative stress played an important role in the process. These results provide an experimental basis for elucidating the molecular mechanisms of the inhibition of acrolein-induced BEAS-2B cytotoxicity with luteolin. Graphical abstract: The regulation of oxidative stress and its related signaling pathways plays a crucial role in the inhibition of BEAS-2B cytotoxicity by luteolin, which is proved by network pharmacology and cell biology techniques. Image 1 Highlights: Network pharmacology analysis indicates that oxidative stress is the crucial pathway. Luteolin restores the oxidation/antioxidant balance against acrolein toxicity. Luteolin inhibits the activation of MAPK/IκBα/NF-κB pathway induced by acrolein. Luteolin suppresses DNA damage and DNA damage response induced by acrolein. GSH plays a key role in luteolin inhibiting acrolein toxicity in BEAS-2B cells.